(untitled) (JULACE: Journal of the University of Namibia Language Centre, 2023)
Academic disciplines are often called discourse communities in research into academic discourse. Citing and referring to other authors in writing shows respect to the intellect of individuals. Students need to cite sources properly in order to be members of the Academic discourse community. This study explored in-text citations in research projects written by first-year students in the Faculty of Education at the University of Botswana. Using Swales’ notion of a discourse community, text analysis and qualitative content analysis, twenty research projects were analysed and three students and two lecturers were interviewed. The findings suggest that students need to be taught the importance of in-text citations and also be assisted to be members of the academic discourse community. There is a need for clear guidelines on citations and regulations for in-text citations and plagiarism for students as soon as they are admitted into their first academic year.